Development Palliative Pharmaceutical Care in Maharaj Nakhonsrithammarat Hospital, Thailand - Aksornwong, Supenporn (Journal of Health Science of Thailand, 2024)
This study aimed to develop a palliative care system at Maharaj Nakhon Si Thammarat Hospital, enabling patients to access high-quality opioids analgesics while meeting the health service system criteria (Service Plan) in the field of palliative care which was set at no less than 40 percent, It also aimed to explore knowledge and understanding of drug use issues, patient behaviors, with a focus on addressing protection of unwanted side effects of medication. The study was conducted as a action research involving problem analysis in collaboration with the patient care team, tool development for system improvement, and following the laid-out system. The study was divided into two periods. The first period, from October 2018 to September 2020, focused on the system for delivering injectable opioids to patients for home use. The results showed that patients access to opioid drugs increased from 5.84% to 20.25%, and 42.60% from the year 2018 to 2020, respectively. All patients could choose to return to pass away at home as per their wishes by receiving injectable opioids pain relief drugs. The second period, from January to September 2020, concentrated on pharmaceutical care by pharmacists at palliative outpatient clinics. Data were collected from March to August 2020, involved 85 patients with 40 males (47.06%), and 45 females (52.94%). The study involved a review of drug use history and medication recommendations of 345 follow-up visits. The most common issue identified was adverse drug reactions, accounting for 45.41% of all medication-related problems out of a total of 262 occurrences, with constipation being the most prevalent (89.07%). The most common reason for non-compliance with medication was the concern about side effects when patients learned that the medication contained opioids (29.41%); and the most common problem regarding medication use was the irregular administering of pain relief drugs (around the clock), with a rate of 27.9%. A system for tracking medication returns was created, with a total value of 62,747.70 baht.